Developing Kindergarten Management System for Supporting the Regional Educational Report - Anita Anita; Sutan Arif Pambudi; Nira Radita; Hilman Nuril Hadi (LPPM STIKI MALANG, 2025)
Administrative tasks in early childhood education centers often face challenges when conducted manually, leading to delays in reporting, data inconsistencies, and limited access for parents. Unlike conventional school management systems, this study specifically targets kindergarten-level reporting that aligns with regional government formats (Korwilkersatdik) in Indonesia. To address these issues, this study focuses on designing and developing a web-based information system to help manage administrative and reporting activities at TK Dharma Wanita 91 Pesanggaran, a kindergarten in Banyuwangi, Indonesia. The research applied a descriptive qualitative method and followed a structured software development process, including system analysis, design, implementation, and evaluation. The system was built using PHP with the CodeIgniter framework and MySQL as the database. It includes modules for student registration, payment validation, attendance tracking, lesson planning, and monthly report generation. Each module was tested using black-box testing and successfully met functional requirements. The implementation of the system significantly reduced manual workload, improved reporting accuracy, and facilitated better communication with parents. The results indicate that the system effectively supports the institution’s operational needs and aligns with reporting standards set by local education authorities. Future development may focus on adding mobile accessibility and analytical features to provide broader access and deeper insights for school management. This study demonstrates how a domain-specific information system can significantly improve the efficiency of kindergarten administration while meeting government reporting standards.